Companion of the the Web Conference 2018 on the Web Conference 2018 - WWW '18 2018
DOI: 10.1145/3184558.3191610
|View full text |Cite
|
Sign up to set email alerts
|

Is this the Era of Misinformation yet

Abstract: Social media is an amazing platform for enhancing public exposure. Anyone, even social bots, can reach out to a vast community and expose one's opinion. But what happens when fake news is (un)intentionally spread within a social media? This paper reviews techniques that can be used to fabricate fake news and depicts a scenario where social bots evolve in a fully semantic Web to infest social media with automatically generated deceptive information. CCS CONCEPTS• Information systems → World Wide Web; Social net… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(19 citation statements)
references
References 20 publications
1
8
0
2
Order By: Relevance
“…Their findings support those from other work demonstrating the difficulty that Twitter users experience in identifying tweets from social bots, which may be due to the informal and short nature of Twitter messages (Freitas, Benevenuto, Ghosh, & Veloso, 2015). Therefore, there exists a potential for bots to leverage interactions with human users to disseminate misinformation and wage disinformation campaigns via social contagion (Wang, Angarita, & Renna, 2018). Studies of Twitter social bot involvement in other topics, including Brexit (UK) and political conversations in Venezuela (Forelle, Howard, Monroy-Hernandez, & Savage, 2015) found that social bots played a less prominent role based on content generated and retweeted.…”
Section: Literature Reviewsupporting
confidence: 81%
“…Their findings support those from other work demonstrating the difficulty that Twitter users experience in identifying tweets from social bots, which may be due to the informal and short nature of Twitter messages (Freitas, Benevenuto, Ghosh, & Veloso, 2015). Therefore, there exists a potential for bots to leverage interactions with human users to disseminate misinformation and wage disinformation campaigns via social contagion (Wang, Angarita, & Renna, 2018). Studies of Twitter social bot involvement in other topics, including Brexit (UK) and political conversations in Venezuela (Forelle, Howard, Monroy-Hernandez, & Savage, 2015) found that social bots played a less prominent role based on content generated and retweeted.…”
Section: Literature Reviewsupporting
confidence: 81%
“…Similarly, Vosoughi et al [56] found that "fake news" articles spread faster on Twitter than true news articles because humans, not bots, were more likely to retweet fake articles. Given human susceptibility to both automated accounts and "fake news," some have warned that intelligent social bots could be leveraged for mass deception or even "political overthrow" [57].…”
Section: How Do Bots Amplify and Spread Misinformation?mentioning
confidence: 99%
“…Almost half (42%) of people sharing news reported having, at least at some point, shared misinformation ( Chadwick and Vaccari, 2019 ). There have been reports of bots being used to increase the visibility of fake news ( Howard et al., 2017 ; Wang et al., 2018 ), as well as attempts to algorithmically detect fake news ( Del Vicario et al., 2016 ). While bot networks spreading this news can be detected and stopped, algorithms cannot, in many cases, distinguish fake news from real news ( Del Vicario et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%